Using human induced pluripotent stem cell-derived cardiomyocytes to understand the mechanisms driving cardiomyocyte maturation - Hamledari, Homa; Asghari, Parisa; Jayousi, Farah; Aguirre, Alejandro; Maaref, Yasaman; Barszczewski, Tiffany; Ser, Terri; Moore, Edwin; Wasserman, Wyeth; Klein Geltink, Ramon; Teves, Sheila; Tibbits, Glen F. (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases are the leading cause of global mortality and reduced quality of life. Human-induced pluripotent stem cells-derived cardiomyocytes (hiPSC-CMs) provide a personalized platform to study inherited heart diseases, drug-induced cardiac toxicity, and cardiac regenerative therapy. However, the immaturity of cardiomyocytes obtained by current strategies is a major hurdle in utilizing hiPSC-CMs at their fullest potential. Here we review the major findings and limitations of current maturation methodologies to enhance the utility of hiPSC-CMs in the battle against the major source of morbidity and mortality.